Antagonistic roles of Drosophila Tctp and Brahma in chromatin remodelling and stabilizing repeated sequences - Sung-Tae Hong (Nature Portfolio, 2016)
Genome stability is important for normal cellular function. Here, Hong and Choi show that translationally controlled tumour protein (TCTP) in Drosophilaregulates pericentromeric chromatin remodelling and transcription via negatively regulating a chromatin remodeler Brahma.